UK research paper of the year. (23rd April 2015) - Hawkes, Nigel
Abstract : The UK Research Paper of the Year category recognises outstanding research by one or more UK authors that has potential to considerably improve health and healthcare. Nigel Hawkes describes the shortlisted papers